El Excentrico, 1960-07-05 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
July 5, 1960 [5 de Julio de 1960]. Ano 10, No 20. Cover has photograph of El Excentrico's publisher and director Humberto Garcia receving an award. The headline reads, "Excentrico receives award dor Meritorious Publicity Service."